Perceptions of parental involvement in youth handball players, the effects of sport participation stage and sports injury - Kovács, Krisztina; Takács, Johanna; Juhász, István; Kovács, Katalin (Frontiers in Psychology, 2024)
Introduction: Globally, from the age of 14, the dropout rate of young athletes is high in all sports games in Hungary. The reasons for dropping out are complex, however parental support is critical to succeed or continue, especially after failure or injury. The present study explored the main effects of sports injury and sport participation stage on parental involvement in sports. Methods: 1174 parents and 690 athletes completed our questionnaire, which contains questions on young players’ sport participation, injury background and Parental Involvement in Sport Questionnaire. Results: Parents’ self-perceived level of involvement differed from the parental involvement perceived by their children. The significant predictors were the person who completed, the parent/athlete, the athlete’s previous sports injury and the child’s current stage of sport participation. In Directive Behavior, the main effect of stages is only seen in parents whose child has been injured. In the sample of injured athletes, the rate of perceived parental Praise and Understanding tends to be lower in the specializing stage. Discussion: Our findings suggest that these two behaviors could be part of the same parenting style, which requires further investigation. The results expand the existing knowledge of the complexity of parents’ involvement in children’s sports careers. These findings have implications beyond parental psychoeducation impacting the work of coaches, sports physicians and rehabilitation experts.